Impacts of climate change on building performance and adaptation solutions - Nguyen Anh Tuan; Phan Anh Nguyen; David Rockwood (Tạp chí Khoa học và Công nghệ)
Climate change has had significant impacts on the global climate, affecting the operational efficiency of buildings. This study employs future climate prediction methods based on the latest IPCC scenarios, using General Circulation Models (GCMs) to forecast climate conditions in three regions of Vietnam. Additionally, the study integrates simulation and simulation-based optimization methods to project the rise in greenhouse gas emissions and the level of thermal discomfort (overheating) in commercial buildings in Vietnam. The findings indicate that, due to the effects of climate change, carbon emissions from commercial buildings in Vietnam could increase by 6% to 22%, while the duration of overheating inside buildings may rise by several tens to several hundred percent.